Students Errors in Reading Indonesian Poetry Aku (I) in Terms of Articulation and StressingIntonation - Surastina, Surastina (International Journal of Active Learning, 2016)
Reading poetry aloud needs special skills, i.e articulating, stressing, and intonating skills, so that the poetry meaning can be well understood by listeners. Those skills must be trained to Indonesian primary student for achieving competencies standard in learning Indonesian poetry. This research aims to describe the students common errors in reading a famous Indonesian poetry entitled Aku by Chairil Anwar. This study was conducted to 120 primary students in Lampung Province, Indonesia which has been randomly chosen by using stratified random sampling technique. The result showed that most of students have low skills in reading poetry as indicated by high percentage of students doing errors. Error in articulating was mainly caused by different student dialect, meanwhile error in stressingintonation were affected by low ability in interpreting poetry and their tendency in reading with spesific pattern. This findings can be used as a reference to evaluate student skills in reading Indonesian poetry.How to CiteSurastina, S. (2016). Students Errors in Reading Indonesian Poetry Aku (I) in Terms of Articulation and StressingIntonation. International Journal of Active Learning, 1(1).